2018
DOI: 10.1074/jbc.ra118.001879
|View full text |Cite
|
Sign up to set email alerts
|

The length of the interleukin-11 receptor stalk determines its capacity for classic signaling

Abstract: Interleukin (IL)-11 is a multifunctional cytokine that was traditionally recognized for its hematopoietic and antiinflammatory functions, but has recently been shown also to be involved in tumorigenesis. IL-11 signaling is initiated by binding of the cytokine to the IL-11 receptor (IL-11R), which is not directly involved in signaling, but required for IL-11 binding to the signal-transducing receptor glycoprotein (gp)130. In classic signaling, IL-11 binds to the membranebound IL-11R in order to initiate signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In classic signaling, IL-11 binds to the membrane-bound IL-11R to initiate signal transduction. Recently, it was found that IL-11 signaling can also be initiated via soluble IL-11R, known as trans-signaling [15]. Upon the formation of IL-11/IL-11R/GP130 hexameric complex, IL-11 mainly mediated cancer development through the induction and activation of the JAK/STAT3 signaling pathway [1618].…”
Section: Introductionmentioning
confidence: 99%
“…In classic signaling, IL-11 binds to the membrane-bound IL-11R to initiate signal transduction. Recently, it was found that IL-11 signaling can also be initiated via soluble IL-11R, known as trans-signaling [15]. Upon the formation of IL-11/IL-11R/GP130 hexameric complex, IL-11 mainly mediated cancer development through the induction and activation of the JAK/STAT3 signaling pathway [1618].…”
Section: Introductionmentioning
confidence: 99%
“…Expression plasmids encoding the IL‐11R variants IL‐11R‐KKSS and IL‐11R‐R296W have been described previously 20 . The IL‐11R deletion variants IL‐11R‐ΔV363_L372 and IL‐11R‐ΔH353_S362 have been described previously 23,39 . All other IL‐11R mutants used in this study were generated via splicing by overlapping extension (SOE)‐PCR using pcDNA3.1‐myc‐hIL‐11R as template.…”
Section: Methodsmentioning
confidence: 99%
“…20 The IL-11R deletion variants IL-11R-ΔV363_L372 and IL-11R-ΔH353_S362 have been described previously. 23,39 All other IL-11R mutants used in this study were generated via splicing by overlapping extension (SOE)-PCR using pcDNA3.1-myc-hIL-11R as template. pcDNA3.1 expression plasmids for hIL-6R have been described previously, 40,41 and a variant with an N-terminal myc-tag was used in this study.…”
Section: Construction Of Expression Plasmidsmentioning
confidence: 99%
“…IL-6 binds the surface formed by the two Fn3 domains, D2 and D3, comprising the CHR ( 68 ). C-terminal of the structured extracellular domains (D1-D3), there is a long linker region (52 residues), predicted to be disordered, that appears to function as a spacer in the signaling complex between the structured extracellular domains and the membrane ( 116 118 ).…”
Section: The Il-6 Family Of Cytokinesmentioning
confidence: 99%